Immobilised catalysts for continuous reactions in supercritical carbon dioxide - Kondor, Bernadett (2010)
This Thesis investigates immobilised metal- and biocatalysts for continuous reactions in scC02. Chemical transformations with high atom economy and low E-factor (amount of waste per kg of product) are highly desired in the green chemical viewpoint. One of the approaches to decrease the production of waste is the use of catalysis (possibly highly selective). Another approach is the use of a 'green' reaction medium as a substitute for traditional solvents that can reduce the production of harmful solvent waste. How this Thesis encompasses by these topics is discussed in Chapter 1. The details of the apparatus, experimental and analytical equipment and procedures are reported in Chapter 2. The field of asymmetric catalytic hydrogenation is a currently important and expanding field of research. In Chapters 3 and 4, the continuous asymmetric hydrogenation of dimethyl itaconate is covered. High enantioselectivity (ees up to 83 %) was obtained in the continuous asymmetric hydrogenation of dimethyl itaconate catalysed by supported homogeneous chiral Rh catalysts on alumina in SCC02 (Chapter 3). This is one of the first examples of the use of chiral catalyst in a continuous flow system without the need for the addition of the chiral modifier. The continuous asymmetric hydrogenation of dimethyl itaconate was also examined with chiral Rh catalysts immobilised in ionic liquids in a biphasic system ionic liquid/scC02 (Chapter 4). High enantioselectivity was achieved in the continuous flow system: ees up to 76 %. Chapter 5 describes the kinetic resolution of secondary alcohols catalysed by immobilised Candida antarctica lipase B (Cal B) in a continuous flow scC02 system. The continuous kinetic resolution of a-tetralol with Cal B immobilised in the form of Cross-Linked Enzyme Aggregate (CLEA) gave excellent enantioselectivity (eeR to 99 %). Different acyl donors (vinyl acetate, phenyl acetate and p-nitrophenyl acetate) were investigated, and were shown to influence the enantioselectivity of the reaction. In Chapter 6, a two step catalytic cascade reaction is described in a continuous flow scC02 system: hydrogenation of acetophenone with a Pd catalyst (Pd Type 31) followed by the kinetic resolution of the product with Cal B CLEA. The series reaction gave good results even when un-optimised: • Step 1 (hydrogenation of acetophenone): conversion up to 91 % • Step 2 (kinetic resolution of (R/S)-l-phenylethanol): conversion of (R)-l-phenylethanol up to 22 %, enantioselectivity (R) > 99 %. Chapter 7 details the preparation of cholesterol oxidase CLEA and combi-CLEA of cholesterol oxidase and catalase, and their application for the continuous oxidation of cholesterol in scC02 with 'in-flow' cholesterol extraction. CLEA were successfully prepared with high retained activity: • Individual cholesterol oxidase CLEA: cholesterol oxidase activity up to 99 % (relative to native), • Combi-CLEA: cholesterol oxidase activity up to 99 % (relative to native), catalase activity up to 53 % (relative to native). Unfortunately, the activity of the CLEA in the continuous oxidation was low, however, the findings of this work will aid in improving the performance of the continuous catalytic oxidation of cholesterol in the future. The possible future directions of this research are presented in Chapter 8.